Magnetization reversal, giant exchange bias effect and magnetoresistance in oxygen vacancy ordered Sr4Fe3CoO11. (9th September 2019) - Mohanty, Prachi; Marik, Sourav; Madhu, C; Singh, D; Toulemonde, O; Singh, Ravi P
Abstract: We report the structural, magnetic, exchange bias, and magnetotransport effect in Sr4 Fe3 CoO11 . The material crystallizes in the orthorhombic space group. It shows antiferromagnetic (G-type) transition ( T N   =  255 K), along with interesting temperature-induced magnetization reversal ( T Comp .   =  47 K measured at 100 Oe). The magnetic reversal can be elucidated considering the increased magnetocrystalline anisotropy with Co substitution. Magnetoresistance measurements show an interesting crossover from the negative to positive side at  ̃100 K. The negative magnetoresistance reaches 80% at 25 K in 7 T magnetic field. Giant exchange bias effect is observed below T N under field cooling condition. The origin of the negative magnetoresistance and giant exchange bias in this sample can be attributed to the magnetic frustration.